Addison's disease associated to paracocidioidomycosis - Claudio Maranhão Pereira; Silmara Regina Silva; Priscila Spaziane Camargo; Andrea Mantesso; Rodrigo Calado Nunes Souza (Universidade Estadual de Campinas, 2015)
Paracoccidioidomycosis is a deep mycosis caused by the Paracoccidioides brasiliensis and it has been considered the most frequent systemic mycosis in Latin America. Mulberry-like ulcers on the oral mucous membranes are one of the earliest manifestations of the disease. Infection may remain subclinical, localized or disseminate occasionally. Adrenal involvement by granulomatous diseases is the main cause of this gland insufficiency in Brazil. The aim of this study is to report one case of oral paracoccidoidomycosis that provided the diagnosis of the systemic mycosis disease with secondary Addison's disease. In spite of not being rare the involvement of the adrenal glands for the P. brasiliensis, it was not possible to find in the literature another case with oral clinical and progression features similar to this.